Ion Pairing and Co‐facial Stacking Drive High‐Fidelity Bisulfate Assembly with Cyanostar Macrocyclic Hosts. Issue 44 (17th July 2017) - Fatila, Elisabeth M.; Twum, Eric B.; Karty, Jonathan A.; Flood, Amar H.
Abstract: Hydroxyanions pair up inside CH H‐bonding cyanostar macrocycles against Coulombic repulsions and solvation forces acting to separate them. The driving forces responsible for assembly of bisulfate (HSO4 − ) dimers are unclear. We investigated them using solvent quality to tune the contributing forces and we take advantage of characteristic NMR signatures to follow the species distributions. We show that apolar solvents enhance ion pairing to stabilize formation of a 2:2:2 complex composed of π‐stacked cyanostars encapsulating the [HSO4 ⋅⋅⋅HSO4 ] 2− dimer and endcapped by tetrabutylammonium cations. Without cations engaged, a third macrocycle can be recruited with the aid of solvophobic forces in more polar solvents. The third macrocycle generates a more potent electropositive pocket in which to stabilize the anti ‐electrostatic anion dimer as a 3:2 assembly. We also see unprecedented evidence for a water molecule bound to the complex in the acetonitrile solution. In methanol, OH H‐bonding leads to formation of 2:1 complexes by bisulfate solvation inside the macrocycles inhibiting anion dimers. Knowledge of the driving forces for stabilization (strong OH⋅⋅⋅O H‐bonding, CH H‐bonding, ion pairs, π‐stacking) competing with destabilization (Coulomb repulsion, solvation) allows high‐fidelity selection of the assemblies. Thermodynamic stabilization of hydroxyanion dimers also demonstrates the ability to use macrocycles to control ion speciation and stoichiometry of the overall assemblies. Abstract : A gathering of stars : Stabilization of an anion–anion dimer results in the formation of higher order assemblies with cyanostar. We discovered that intermolecular forces such as ion pairing, solvophobic effects, and ion solvation control the speciation in solution. We demonstrate the ability to control ion speciation and stoichiometry by simple solvent variation.